Characteristics of brand value and its application by tourism enterprises - Авдан, Оксана Григорівна (Technology audit and production reserves, 2015)
Brand using of a tour operator and travel agent has been analyzed. Method of calculating the discount rate coefficient through BrandBeta has been researched, taking into account the dynamics of the brand development. The features using four brands of tour operators in fifty two travel agents’ brands from seven Ukrainian regions has been researched, indicating that the most expensive brand is Tez Tour. It has been determined, that the presence of the brand gives tourism enterprises certain benefits: it allows to earn additional revenue; protects manufacturer of tourism cervices while cooperating with partners; facilitates consumer choice among tourism products; identifies the tourism enterprise and its services among tourism products of competitors; facilitates entrance to the related markets with new products; gives an opportunity to invest in the future. It has been investigated, that to increase sales of travel packages and increase their own profits, travel agents need to make their own individual image among consumers in the competitive environment of numerous travel agencies.